REPRESENTATION OF WOMEN AS OBJECTS OF CONSUMERISM (CRITICAL DISCOURSE ANALYSIS ON PAYLATER SERIES IN EPISODES 1 AND 2) - Tripalupi, Merry Fridha; Irawan, Rahmat Edi; Duile, Timo (ASPIKOM Jabodetabek Region, 2025)
Impulsive buying behavior is increasingly becoming a trend after the existence of marketplaces that make it easier for consumers to buy an item. Currently, active e-commerce users in Indonesia continue to grow with increasingly massive digital activities. Fashion is an item that is more purchased by women in online shopping. The persuasion of advertisements featuring products that claim to perfect women's appearance is a hot-selling commodity. The depiction of the entanglement of consumerism is shown in the Pay Later series. This series tells the story of Tika, the main character, who becomes the object of consumerism. By using the critical discourse analysis method of Sara Mills, which focuses on feminism and in line with this research, which is based on the theory of postmodern feminism, the results show the subject-object position that this series provides an overview of women as objects of consumerism where looking beautiful with beautiful goods is a requirement for women to look more attractive. The use of pay later, which provides flexibility in terms of payment, is attractive to the main character without being accompanied by adequate financial literacy skills. This is what makes the main character get entangled in paying later debt. The high interest rate and relatively short deadline are the problems that are then faced. For the sake of appearing charming, the main character is haunted by debt collectors in his daily life.